A Study Employees' Intention to Stay in Kedah State Development Corporation, Kedah, Malaysia - Wang, Wei (2011)
The main objective of this study is to examine the factors to influence employees’ retention intention in Kedah State Development Corporation (KSDC). The five factors that to measure employees’ retention intention were compensation, work-life balance, organizational commitment, career opportunity and supervisor support. Data were gathered through questionnaire survey of employees at KSDC Company (n=92). Correlation and regression analysis were used of examine the relationship between the five factors and employees’ retention intention. The results indicated that compensation, work-life balance, organizational commitment, career opportunity and supervisor support were positively correlated with employees’ intention to stay in the KSDC Company. The multiple regression results suggest that compensation was the most important factor in influencing employees’ retention intention. The findings were discussed and recommendations for further research were also addressed.